2018
DOI: 10.1111/bph.14488
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the tumour micro‐environment communication network from an NOS2/COX2 perspective

Abstract: Recent findings suggest that co-expression of NOS2 and COX2 is a strong prognostic indicator in triple-negative breast cancer patients. These two key inflammation-associated enzymes are responsible for the biosynthesis of NO and PGE , respectively, and can exert their effect in both an autocrine and paracrine manner. Impairment of their physiological regulation leads to critical changes in both intra-tumoural and intercellular communication with the immune system and their adaptation to the hypoxic tumour micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 252 publications
(283 reference statements)
1
28
0
Order By: Relevance
“…Low flux of NO produced via NOS3 has been demonstrated to activate MEK-ERK and JAK-STAT pathways [44], and activation of these pathways is known to induce pro-metastatic and CSC-related genes [[45], [46], [47], [48], [49], [50]]. NOS2 is also known to activate MEK-ERK and PI3K-AKT pathways [51], which can induce CSC related genes [[45], [46], [47],51,52]. Thus, MEK-ERK, JAK-STAT and PI3-AKT pathways may be important in INV.…”
Section: Resultsmentioning
confidence: 99%
“…Low flux of NO produced via NOS3 has been demonstrated to activate MEK-ERK and JAK-STAT pathways [44], and activation of these pathways is known to induce pro-metastatic and CSC-related genes [[45], [46], [47], [48], [49], [50]]. NOS2 is also known to activate MEK-ERK and PI3K-AKT pathways [51], which can induce CSC related genes [[45], [46], [47],51,52]. Thus, MEK-ERK, JAK-STAT and PI3-AKT pathways may be important in INV.…”
Section: Resultsmentioning
confidence: 99%
“…Previous data suggested that co-expression of NOS2 and COX2 is a strong prognostic indicator in TNBC patients [66], also contributing to tumor aggressiveness and poor patient prognosis [67].…”
Section: Discussionmentioning
confidence: 99%
“…The notion of communication through intercellular signaling has classically involved structure-function interactions. In addition, redox regulated signaling has provided new strategies to enhance cancer therapy that have included modification of signal transduction, immune signaling, inhibition of nitric oxide synthase 2 (NOS2), and cyclooxygenase 2 (COX2), which have all shown promise in preclinical and even clinical trials [4][5][6]. Furthermore, NOS2/COX2 are linked to poor outcome and collaborate in feedforward loops in both cancer and immune cells in several tumor types, with ER-breast cancer being the best example [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%